Association Between Work-Related Factors and Diet: A Review of the Literature. (March 2019) - Tanaka, Rie; Tsuji, Mayumi; Tsuchiya, Takuto; Kawamoto, Toshihiro
The quality of workers' dietary intake could be influenced by their working conditions. This review aimed to summarize the published literature examining the association between work-related factors, such as work hours, shift work, physical strain, mental strain, job strain, support, and diet quality. The literature search, conducted in PubMed, was limited to articles published from 2000 to 2017, written in English, available online, and among workers employed in high-income countries. The search resulted in 16 articles that met the criteria. Although there was some evidence of unhealthy diet among shift workers, data on the diet quality in association with other work-related factors, such as number of hours worked, physical, mental, and job strain, and worksite support were scarce. Further studies are need for purposes better defining the association between work-related factors and quality of workers' diet.